2020
DOI: 10.47104/ebnrojs3.v2i4.159
|View full text |Cite
|
Sign up to set email alerts
|

Chest Tube Removal: Efficacy of Cold Application and Breathing Exercise on Pain and Anxiety Level

Abstract: Context: Post-cardiothoracic surgical chest tube removal (CTR) is considered a painful technique and one of the most painful patients' experiences in the intensive care unit. Painkillers are the most prevalent method to relieve the pain, but the patient may not respond well and achieved complete relaxation. Regardless of scientific advances, no efficient action is possessed to decrease pain and anxiety because of it. Aim: This study aimed to investigate the efficacy of cold application and breathing exer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…In this study, the pre-procedure baseline pain scores of the intervention and control groups were found to be similar. Similarly, it is reported in the literature that there is no significant difference between the groups in terms of pain score before ChTR [20][21][22][23][24][25][26][27].…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…In this study, the pre-procedure baseline pain scores of the intervention and control groups were found to be similar. Similarly, it is reported in the literature that there is no significant difference between the groups in terms of pain score before ChTR [20][21][22][23][24][25][26][27].…”
Section: Discussionsupporting
confidence: 56%
“…While there was no difference in the anxiety scores of the groups before the procedure, Aktaş and Karabulut [33] reported in their study that there was no difference between the preprocedure anxiety scores of the groups treated with cold therapy, music therapy, and lidocaine spray during the ChTR procedure and the control group. Elmetwalyl and Sayed [22] found that anxiety scores were similar in the intervention cold application and relaxation exercise) and control groups before the ChTR procedure. Similar results were obtained in other studies in the literature [21,27].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Also Majority of the patient in were married (80%). Table (4) illustrates that the majority of the studied patients had undergone valve surgery (55%). It also illustrates that (46.7%) in the studied patients had mediastinal chest tube.…”
Section: Field Workmentioning
confidence: 99%
“…Breathing exercise by changing breathing depth and frequency (Brown et al, 2013), as one type of nonpharmacological interventions, has demonstrated the benefit of pain relief in various conditions (Elmetwaly & El Sayed, 2020;Purnamasari et al, 2020;Sasongko et al, 2019). Although clear mechanisms of the breathing exercises for pain reduction have not yet been established, the proposed baroreflex theory posits that breathing manipulation can activate baroreflex, which leads to decreased pain sensitivity (Hassan Jafari et al, 2017).…”
Section: Introductionmentioning
confidence: 99%